Pengaruh Program Habituasi terhadap Kondusifitas Lingkungan Sekolah - Iqbal, Muhammad; Watun, Baiq Ririn Rizza; Hariawan, Rudi; Fahmi, Agus (Realita : Jurnal Bimbingan dan Konseling, 2023)
This study aims to determine the effect of the habituation program on the conduciveness of the school environment at SMA Negeri 1 Sikur East Lombok. The population in this study were students of class X and XI. The data analysis technique used in this study was descriptive statistics and simple regression analysis. The results of this study indicate that the habituation program has a significant effect on the conduciveness of the school environment. This is evidenced by the analysis results obtained that the r-count value (0.73) is greater than the r-table value (0.53). The results of the regression equation analysis obtained a value of 3.19 while the F-count value was obtained at 112.891 and the t-count value was obtained at -0.96 with a significance level of 0.000 > 0.05. The R2 value was obtained at 0.535 or 53.5%. This shows that there are other factors that affect 46.5% which are not discussed or examined in this study. Based on these results, it means that the proposed hypothesis is accepted or Ho is rejected and Ha is accepted which reads that the habituation program has a significant effect on the conduciveness of the school environment in SMA Negeri 1 Sikur, East Lombok.